Intraperitoneal injection but not oral administration of ellagic acid: a novel immunomodulator via targeting casein kinase 2 signaling pathway - Wenhui Qi; Bing Han; Tingting Cui; Peixin Shen; Zhuohua Zhao; Yaping Yan; Libin Wang; Xinyu Lu; Yuan Zhang; Xing Li (Food Science and Human Wellness)
Immunosuppressants currently approved for the treatment of autoimmune diseases and organ transplant rejection present diverse adverse effects that impair the life quality of patients. Therefore, the development of novel immunomodulators with high efficiency and low toxicity is essential. Ellagic acid (EA), a natural polyphenol compound widely distributed in berries, is metabolically transformed by gut microbiome to exert systemic health benefits. Here, we identified that intraperitoneal administration of EA with no cytotoxicity, beyond its well-known oral metabolic fate, effectively decreased clinical severity and central nervous system (CNS) inflammation/demyelination in experimental autoimmune encephalomyelitis, a mouse model of an autoimmune disease multiple sclerosis. Interestingly, intraperitoneal EA administration at incredibly low doses (0.1 mg/(kg·day)) is dose-sparing with fingolimod (FTY720), the first FDA-approved oral drug for MS. In addition, intraperitoneal EA also ameliorated the brain damage in a neuromyelitis optica (NMO) model, and significantly prevented the immune rejection of allograft skin graft. Evidence from pharmacological studies combined with RNA-seq indicate that prototype EA functions by a mechanism that involves direct inhibition of casein kinase Ⅱ (CKⅡ) to suppress the expression of IL-17 and promote the expression of Cpt1a to regulate T helper cell 17 differentiation. In conclusion, our study demonstrates that the prototype EA entering the blood circulation acts as a novel therapeutic immunomodulator for the treatment of autoimmune diseases and transplant rejection through the CKⅡ-mediated Janus kinase/signal transducer and activator of transcription 3 Cpt1a signaling pathway.